Muscle and liver protein synthesis and degradation in growing rats fed a raw field bean (Vicia faba L.) diet (Revista Española de Fisiología, 1988)
Body weight gain, food intake, gastrocnemius muscle and liver weight, protein and RNA content, as well as the fractional rates of muscle and liver protein synthesis (ks, according to the method of constant infusion of L-[14C]tyrosine), growth (kg) and degradation (kd), along with RNA activity (g of protein synthesized per day/g RNA) of both organs, were determined in growing male rats fed ad libitum over a period of 10 days on 18.7% protein diets containing either casein (5% of methionine added) (control) or the raw legume field bean (Vicia faba L.) as the sole sources of protein.It has been found that as compared to control rats, those fed the raw legume diet exhibited a significant reduction in the rate of growth, muscle RNA, ks, kg, kd and RNA activity, and a significant increase in liver ks, kd and RNA activity.All differences were statistically significant at least at the 5% level.The possible nature of these findings is discussed.